2003
DOI: 10.1074/jbc.m211325200
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Arachidonate-releasing Function of Novel Classes of Secretory Phospholipase A2s (Groups III and XII)

Abstract: 2 exhibited abnormal morphology, suggesting a unique functional aspect of this enzyme. Based on the present results as well as our current analyses on the group I/II/V/X sPLA 2 s, general properties of cellular actions of a full set of mammalian sPLA 2 s in regulating AA metabolism are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 77 publications
3
78
0
Order By: Relevance
“…4 and 5). Reportedly, PLA2G2F shows a ϳ2-fold preference for arachidonic acid over linoleic acid in vitro (63), and its ability to hydrolyze PC is similar to that of PLA2G3 both in vitro and in cultured cells (18). Although the pathophysiological relevance of these observations is still unclear, a recent study has shown the inducible expression of PLA2G2F (in addition to several other sPLA 2 s) in human atherosclerotic plaques (40).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…4 and 5). Reportedly, PLA2G2F shows a ϳ2-fold preference for arachidonic acid over linoleic acid in vitro (63), and its ability to hydrolyze PC is similar to that of PLA2G3 both in vitro and in cultured cells (18). Although the pathophysiological relevance of these observations is still unclear, a recent study has shown the inducible expression of PLA2G2F (in addition to several other sPLA 2 s) in human atherosclerotic plaques (40).…”
Section: Discussionmentioning
confidence: 96%
“…The central S domain alone is sufficient for its enzymatic function (17)(18)(19). PLA2G3 undergoes proteolytic processing to produce the S domain-only form in cultured cells (19), yet it remains uncertain whether the same processing occurs in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Materials-Culture of human embryonic kidney (HEK) 293 cells, human colon adenocarcinoma HCA-7 cells, human lung epithelial BEAS-2B cells, and rat fibroblastic 3Y1 cells in RPMI1640 medium (Nissui Pharmaceutical Co.) supplemented with 10% fetal calf serum was described previously (14,22,29,30). The cDNAs for human mPGES-1 (14), human COX-1 and COX-2 (4), and monkey mPGES-2 (28) were described previously.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, as depicted in Figure 5, this sequence matched Group III PLA2s from the insects D. melanogaster (gi|21627771) and A. mellifera (gi|16904372), from the venom of the gila monster Heloderma suspectum (gi|104338), and from the scorpions Anuroctonus phaiodactylus (gi|46484897) and Pandinus imperator (gi|37079101), as well as a Group IX PLA2 toxin from the marine medusa Rhopilema nomadica (gi|999133). Furthermore, LOqua-PLA1 also displays homology to the carboxy domain of human Group III PLA2 (gi| 7657126) whose function is related to arachidonate release from cells (Murakami et al, 2003). At present, the substrate specificity and function for this putative secreted PLA2 is a matter of speculation, but it may be somehow involved in the hemolysis observed after envenomation (Seibert et al, 2004).…”
Section: Phospholipase A2 (Pla2)-phospholipasesmentioning
confidence: 99%